AB0062 Trem-1 expression induced by vitamin D3 in human monocytes/macrophages. (23rd January 2014) - Ji, J.D.; Lee, B.; Kim, T.-H.; Kwon, E.; Choi, S.J.; Lee, Y.H.; Sohn, J.; Song, G.G.
Abstract : Background: Triggering receptor expressed on myeloid cells-1 (TREM-1) is a recently identified cell surface receptor that is expressed mainly on monocytes and neutrophils, and plays a role as an amplifier of immune response. Recent studies suggested that TREM-1 may play an important role in the pathogenesis of chronic inflammatory diseases such as rheumatoid arthritis (RA) and inflammatory bowel disease (IBD). TREM-1 expression is strongly upregulated by inflammatory stimuli such as lipopolysaccharide (LPS) and prostaglandin E2 (PGE2). Objectives: In this study, we investigated the regulation of TREM1 expression in human monocyte/macrophages. Also, we examined the effects of vitamin D3 on TREM-1 expression in human monocyte/macrophages. Methods: Gene expressions were analyzed using real-time PCR and cell surface expression of TREM-1 was analyzed by flow cytometry. Results: In human peripheral monocytes, TREM-1 is highly expressed and TREM-1 expression is down-regulated during differentiation into macrophages. In these cells, lipopolysaccharide (LPS) and TNFa, but not IL-1b stimulate TREM-1 expression. In addition to inflammatory molecules such as LPS and TNFa, 1, 25-Dihydroxyvitamin D3 (1, 25(OH)2 D3 )strongly upregulated the expression of TREM-1 in human monocyte/macrophages. Also TREM-1 expression was upregulated by 1, 25(OH)2 D3 in synovial fluid macrophages from RA patients. We found that 1, 25(OH)2 D3 stimulates TREM-1 mRNA expression by augmenting transcription, not by inhibiting mRNA degradation. The upregulated expression of TREM-1 by 1, 25(OH)2 D3 was partially dependent on p38 MAPK and NF-κB activation, and required new protein synthesis. Finally, 1, 25(OH)2 D3 augments TREM-1-stimulated IL-1β expression in the presence of LPS suggesting that vitamin D3 -induced TREM-1 is functional. Conclusions: Our results show that 1, 25(OH)2 D3 can affect the innate and inflammatory responses by up-regulating TREM-1 expression, and suggest the possibility that 1, 25(OH)2 D3 may be function as an enhancer of innate immune response in chronic inflammatory conditions. Disclosure of Interest: None Declared